2019
DOI: 10.1097/rnj.0000000000000211
|View full text |Cite
|
Sign up to set email alerts
|

Using Volume-Based Tube Feeding to Increase Nutrient Delivery in Patients on a Rehabilitation Unit

Abstract: Purpose The purpose of this study was to determine whether volume-based tube feeding (VBTF) increased nutrient delivery to patients in a rehabilitation unit. Design A cohort study with a prospective group and a historical control group was used as the study design. Methods The intervention was VBTF, a change from the standard hourly rate-based enteral nutrition. Data were collected on 70 rehabilitation patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…18,29,33,35,36 Ward-based literature includes a recent cohort study investigating VBF in a medical rehabilitation unit. 37 Compared to our study, these authors found similar RBF EN adequacy (67%) but a lower improvement in their VBF intervention group (92% vs. 82%). 37 This may be due to their lower maximum feeding rate (150 ml/h), limited ongoing staff education or undefined catch-up feeding times.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…18,29,33,35,36 Ward-based literature includes a recent cohort study investigating VBF in a medical rehabilitation unit. 37 Compared to our study, these authors found similar RBF EN adequacy (67%) but a lower improvement in their VBF intervention group (92% vs. 82%). 37 This may be due to their lower maximum feeding rate (150 ml/h), limited ongoing staff education or undefined catch-up feeding times.…”
Section: Discussioncontrasting
confidence: 61%
“…37 Compared to our study, these authors found similar RBF EN adequacy (67%) but a lower improvement in their VBF intervention group (92% vs. 82%). 37 This may be due to their lower maximum feeding rate (150 ml/h), limited ongoing staff education or undefined catch-up feeding times. 37 In contrast, our study integrated a protocol with predefined time points for catch-up feeding (12:00 PM and 6:00 PM) and a comprehensive education with nurse-led champions.…”
Section: Discussioncontrasting
confidence: 61%
“…For example, results of studies comparing volumebased with rate-based feeding protocols report a significant improvement in percentage of calorie requirements delivered. [7][8][9][10][11] Sachdev et al observed a significant difference in percentage of calorie delivery between the volumebased (73%) and rate-based feeding groups (65%); the effect size for this difference in calorie delivery is 0.6, typically indicating a medium effect. 8 However, in this example, the difference in percentage of calorie delivery methods was only 8%, which may not be considered a moderate, or medium, change.…”
Section: Effect Sizementioning
confidence: 99%
“…Studies with a small effect size may have clinically meaningful outcomes, whereas studies with a large effect size may not provide a relevant result. For example, results of studies comparing volume‐based with rate‐based feeding protocols report a significant improvement in percentage of calorie requirements delivered 7–11 . Sachdev et al observed a significant difference in percentage of calorie delivery between the volume‐based (73%) and rate‐based feeding groups (65%); the effect size for this difference in calorie delivery is 0.6, typically indicating a medium effect 8 .…”
Section: Effect Sizementioning
confidence: 99%
See 1 more Smart Citation